1984
DOI: 10.1210/endo-114-2-441
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Subserving Calcium’s Modulation of Luteinizing Hormone Action in Isolated Swine Granulosa Cells*

Abstract: We studied the mechanism(s) by which calcium ions modulate progesterone biosynthesis by isolated swine granulosa cells incubated in chemically defined medium in vitro. In selectively calcium-deficient incubations, the capacity of 8-bromo-cAMP to stimulate pregnenolone synthesis from endogenous sterol substrate was significantly impeded. This effect of calcium ions was specific, because calcium ions did not influence basal pregnenolone production or alter progesterone production in response to exogenously suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Basal progesterone production of cadmium-treated cells remained unchanged (20 ng/ml) or was enhanced; this supports the theory of cadmium -calcium competition. Calcium has been reported not to influence basal pregnenolon production or estrogen synthesis from androgen substrates, or progesterone production from exogenously supplied sterol substrates in porcine granulosa cells whereas it is known that calcium ions influence the stimulatory action of LH and modulate the effects of cAMP on progesterone biosynthesis (Veldhuis et al 1984).…”
Section: Discusssionmentioning
confidence: 98%
“…Basal progesterone production of cadmium-treated cells remained unchanged (20 ng/ml) or was enhanced; this supports the theory of cadmium -calcium competition. Calcium has been reported not to influence basal pregnenolon production or estrogen synthesis from androgen substrates, or progesterone production from exogenously supplied sterol substrates in porcine granulosa cells whereas it is known that calcium ions influence the stimulatory action of LH and modulate the effects of cAMP on progesterone biosynthesis (Veldhuis et al 1984).…”
Section: Discusssionmentioning
confidence: 98%
“…The results that the ovarian CR activity and its concentration in Px-F1 rats, which had regular cyclicity, were higher than those in normal rats, which had persistent estrus, indicate that the maternal parathyroidectomy may positively influence the hypothalamo-pituitary-ovarian axis in the female offspring. Furthermore, Veldhuis et al (21) have reported that an inhibitor of intracellular calcium mobilization and calmodulin antagonists inhibit LH-stimulated progesterone production and suggested that calcium ions modulate LH action in ovarian cells in part by a calciumcalmodulin-dependent mechanism. Accordingly, the altered calcium metabolism during the fetal life may cause the delayed onset of persistent estrus in Px-F1 female rats.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the stimulatory effects of PGE1 and hCG on adenylate cyclase activity in the Leydig cells of rats (30-40 days of age) are biphasically regulated by calcium ions (8) and that calcium ions modulate LH ac tion in swine granulosa cells (10). Wiltbank et al (23) sug gested that the luteolytic action of PGF2a in the large lu teal cells may be mediated by intracellular calcium by ac tivating protein kinase C, inactivating adenylate cyclase, decreasing cAMP phosphodiesterase activity and decreas ing various metabolic enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium ions appear to play an important role in gonadotropin-induced steroidogenesis as well as the ac tion of cyclic AMP in ovary and testis (7)(8)(9)(10)(11). Janszen et al (7) have shown that calcium ion potentiates the effect of LH on testosterone production in a suspension of whole interstitial cells from rat testis.…”
mentioning
confidence: 99%